The candy smash - Davies, Jacqueline, 1962- (Boston : Houghton Mifflin Books for Children, 2013)
"Explores the distinctive power of poetry and love--fourth grade style"--
Keywords: Poetry -- Juvenile fiction; Man-woman relationshiips -- Juvenile fiction; Schools -- Juvenile fiction; Siblings -- Juvenile fiction; Poetry -- Fiction; Love -- Fiction; Schools -- Fiction; Brothers and sisters -- Fiction